2007
DOI: 10.1183/09031936.00015307
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory symptoms, atopy and bronchial hyperreactivity in professional firefighters

Abstract: The aim of the present study was to assess respiratory health in professional firefighters.A total of 101 male professional firefighters from Basel, Switzerland, were included in the study. A control group consisting of 735 male subjects of the general population was composed of the Basel sample of the Swiss Study on Air Pollution and Lung Diseases in Adults. All subjects were administered a standardised questionnaire, spirometry, skin-prick tests and bronchial challenge testing to methacholine.Respiratory sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
3
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 57 publications
(80 reference statements)
1
36
3
6
Order By: Relevance
“…Studies that assessed BHR among firefighters were mostly confined to acute response (5,11) or the respiratory sequelae of the World Trade Center disaster (12, 13). Although Miedinger et al (6) found a higher prevalence of BHR in firefighters compared to a general Swiss population, a relation to length of employment as exposure estimate could not be demonstrated. However, in our study we found a positive relation between number of fires fought in the last 12 months and BHR (β=0.146, P=0.03) adjusted for smoking.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Studies that assessed BHR among firefighters were mostly confined to acute response (5,11) or the respiratory sequelae of the World Trade Center disaster (12, 13). Although Miedinger et al (6) found a higher prevalence of BHR in firefighters compared to a general Swiss population, a relation to length of employment as exposure estimate could not be demonstrated. However, in our study we found a positive relation between number of fires fought in the last 12 months and BHR (β=0.146, P=0.03) adjusted for smoking.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have indicated that smoke exposure may result in acute lung function impairment (3,4) and acute increase of airway responsiveness (5). Furthermore, studies have suggested that firefighters are at risk of chronic respiratory symptoms and lung function impairment (6)(7)(8). On the other hand, some studies did not find associations between exposure and lung function impairment (9,10).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Earlier studies have indicated that exposure of firefighters to smoke may result in acute lung function impairment [Musk et al, 1979; Brandt‐Rauf et al, 1989; Large et al, 1990], acute increase of airway responsiveness [Chia et al, 1990], and acute increase of respiratory symptoms [Betchley et al, 1997]. Furthermore, studies have suggested that firefighters are at risk of chronic respiratory symptoms and lung function impairment [Mustajbegovic et al, 2001; Miedinger et al, 2007; Ribeiro et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Acute exposure induces acute neutrophilic inflammation and chronic systemic inflammation, and bronchial hyperreactivity develops (16). Atopy, asthma, and asthma attack prevalence significantly increase (12,17,18). Smoke exposure may result in acute bronchitis, chronic obstructive pulmonary disease, chronic interstitial pneumonia, pulmonary arterial hypertension, and interstitial lung disease (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%